1997
DOI: 10.1073/pnas.94.15.7799
|View full text |Cite
|
Sign up to set email alerts
|

Evolution by the birth-and-death process in multigene families of the vertebrate immune system

Abstract: Concerted evolution is often invoked to explain the diversity and evolution of the multigene families of major histocompatibility complex (MHC) genes and immunoglobulin (Ig) genes. However, this hypothesis has been controversial because the member genes of these families from the same species are not necessarily more closely related to one another than to the genes from different species. To resolve this controversy, we conducted phylogenetic analyses of several multigene families of the MHC and Ig systems. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

35
565
0
6

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 733 publications
(606 citation statements)
references
References 76 publications
35
565
0
6
Order By: Relevance
“…This observation suggests that the more gene duplications occur, the more IGHV pseudogenes are generated in the IGHV multigene family. Previously, Nei and coworkers (Nei et al 1997;Nei and Hughes 1992;Nei and Rooney 2005;Nozawa and Nei 2007) showed that in many multigene families, gene duplication often occurs, but because of deleterious mutations, many duplicate genes become nonfunctional and either stay in the genome as pseudogenes or are gradually eliminated from the genome by unequal crossing over. Although the number of deleted IGHV pseudogenes cannot be assessed easily, our results suggest that throughout IGHV evolution, the numbers of functional and nonfunctional genes are maintained by birth-and-death evolution.…”
Section: Discussionmentioning
confidence: 99%
“…This observation suggests that the more gene duplications occur, the more IGHV pseudogenes are generated in the IGHV multigene family. Previously, Nei and coworkers (Nei et al 1997;Nei and Hughes 1992;Nei and Rooney 2005;Nozawa and Nei 2007) showed that in many multigene families, gene duplication often occurs, but because of deleterious mutations, many duplicate genes become nonfunctional and either stay in the genome as pseudogenes or are gradually eliminated from the genome by unequal crossing over. Although the number of deleted IGHV pseudogenes cannot be assessed easily, our results suggest that throughout IGHV evolution, the numbers of functional and nonfunctional genes are maintained by birth-and-death evolution.…”
Section: Discussionmentioning
confidence: 99%
“…19 Gene death appears to be in progress for the pseudogenes DEFB122p and DEFB109p 4 following the 'birth and death' mechanism, which is well known in the Ig and MHC multigene families. 35 Molecular evolutionary analysis suggests that the diverse cluster of defensin paralogs at 20q evolved by tandem duplication of individual genes rather than groups. All of these duplications occurred long prior to the human-macaque split, which is thought to have occurred more than 23 million years ago.…”
Section: Discussionmentioning
confidence: 99%
“…A recent addition to the body of evidence supporting the single early evolution of venom in snakes has been the use of protein amino acid or DNA gene sequences from toxins, and their homologues among non-venom body proteins 6,7 . Venom toxins belong to multiple multi-locus gene families, evolving according to the birth and death model 8 , and first acquired their role within venom following recruitment from protein families fulfilling ordinary physiological functions 9 . Mapping the gene tree of these protein families onto the corresponding organismal tree allows the reconstruction of the history of the recruitment of the toxin into the venomous arsenal of the animals.…”
mentioning
confidence: 99%